Anthelmintic properties of traditional African and Caribbean medicinal plants: identification of extracts with potent activity against Ascaris suum in vitro - Williams Andrew R.; Soelberg Jens; Jäger Anna K. (Parasite, 2016)
Ascariasis affects more than 1 billion people worldwide, mainly in developing countries, causing substantial morbidity. Current treatments for Ascaris infection are based on mass drug administration (MDA) with synthetic anthelmintic drugs such as albendazole, however continual re-infection and the threat of drug resistance mean that complementary treatment options would be highly valuable. Here, we screened ethanolic extracts from 29 medicinal plants used in Africa (Ghana) and the Caribbean (US Virgin Islands) for in vitro anthelmintic properties against Ascaris suum, a swine parasite that is very closely related to the human A. lumbricoides. A wide variety of activities were seen in the extracts, from negligible to potent. Extracts from Clausena anisata, Zanthoxylum zanthoxyloides and Punica granatum were identified as the most potent with EC50 values of 74, 97 and 164 μg/mL, respectively. Our results encourage further investigation of their use as complementary treatment options for ascariasis, alongside MDA.